2013
DOI: 10.5897/ijnm2013.0100
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making for use of complementary and alternative therapies by pregnant women and nurse midwives during pregnancy: An exploratory qualitative study

Abstract: Millions of people use complementary and alternative medicine (CAM) therapies. Such therapies are used across a wide spectrum of health conditions, but the use is particularly notable during pregnancy. Despite the widespread use, little is known about the perceptions of patients and clinicians in deciding about use of varied therapies. This study describes pregnant women and obstetrical provider (nurse midwives) perceptions in decision-making for use of CAM therapies during pregnancy. Pregnant women and nurse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Self-determination in health care choices may influence pregnant or breastfeeding mothers’ choices to use CMPs [1316], especially in relation to desiring holistic health care [15]. Common reasons given for mothers’ use of CMPs include t reatment of common conditions of pregnancy or lactation [3, 17, 18], to prepare for a natural childbirth [13, 16, 19], and to support and maintain health [20] or breastmilk production [3, 17, 21]. Other factors identified that have been associated with use of complementary therapies, including CMPs, in pregnancy include cultural factors, positive experiences with previous use, and perceptions that complementary medicines may be a safer choice than pharmaceutical medications [16, 22].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Self-determination in health care choices may influence pregnant or breastfeeding mothers’ choices to use CMPs [1316], especially in relation to desiring holistic health care [15]. Common reasons given for mothers’ use of CMPs include t reatment of common conditions of pregnancy or lactation [3, 17, 18], to prepare for a natural childbirth [13, 16, 19], and to support and maintain health [20] or breastmilk production [3, 17, 21]. Other factors identified that have been associated with use of complementary therapies, including CMPs, in pregnancy include cultural factors, positive experiences with previous use, and perceptions that complementary medicines may be a safer choice than pharmaceutical medications [16, 22].…”
Section: Introductionmentioning
confidence: 99%
“…Common reasons given for mothers’ use of CMPs include t reatment of common conditions of pregnancy or lactation [3, 17, 18], to prepare for a natural childbirth [13, 16, 19], and to support and maintain health [20] or breastmilk production [3, 17, 21]. Other factors identified that have been associated with use of complementary therapies, including CMPs, in pregnancy include cultural factors, positive experiences with previous use, and perceptions that complementary medicines may be a safer choice than pharmaceutical medications [16, 22]. Many women feel a responsibility to bear healthy children, leading to balancing what they perceive as possible harms to the health of their unborn or breastfeeding babies and themselves while also considering their health care practitioners’ (HCPs’) advice [22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies showed that the women had a positive opinion on the safety of herbal remedies during pregnancy [ 16 , 17 ]. Moreover, a minimum of one-third of the healthcare professionals are willing to recommend the use of CAM to pregnant women [ 18 , 19 ], and the majority (69.2%) agreed that there was some value in CAM use during pregnancy [ 20 ].…”
Section: Introductionmentioning
confidence: 99%